I assume you want the CDF of Y, not X.
I have this question i cant nut out
f(x)=3/32(4-x^2) when -2<x<2
hence F(x)=0 when -2>x
(3/8)x-(x^3)/32+1/2 when -2<x<2
1 when 2<x
let Y=(X^2)+1, find the CDF of Y
Heres my (probably wrong method or something) working out:
Fy(y)=P(Y<y)=P((x^2+1)<y)=P(X<sqrt(Y-1))=Fx(sqrt(y-1))
therefore Fy(y)=3/8(sqrt(y-1))^(1/2)-((sqrt(y-1))^3)/32+1/2
this isn't a proper CDF when i checked graphing it...
Any help would be appreciated
Edit: yeah, my mistake, i want the CDF of Y